Studi Narasi Mengenai Penahbisan Tembok Yerusalem Menurut Nehemia 12:27-43 - Farel Yosua Sualang (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2020)
The Meaning of the Ordination of the Jerusalem Wall in Nehemiah 12: 27-43 discusses two processes, each of which was led by a group of choirs, traveling from the opposite direction along the upper part of the vast wall. The Israelites met in the Temple area and ended with thanksgiving and sacrifices. This scientific work uses a text research methodology with a specific narrative genre in the form of story reports. The report on the dedication of the walls of Jerusalem does not reveal a problem or a resolution. The text only describes the sequence of events (facts) in the dedication of the walls of Jerusalem. The dedication ceremony for the Jerusalem wall was a report from Nehemiah. The text of Nehemiah 12: 27-43 only describes events that occurred during the celebration of the dedication of the walls of Jerusalem. The theological significance in the Ordination of the Jerusalem Wall according to Nehemiah 12: 27-43 shows the role of God (God gives joy, God guides the repair of Jerusalem's walls), the importance of giving thanks, and the importance of God's people in praising God. Abstrak Indonesia Makna penahbisan Tembok Yerusalem dalam Nehemia 12:27-43 membahas dua proses, yang masing-masing dipimpin oleh sekelompok paduan suara, yang berjalan dari arah berlawanan di sepanjang bagian atas tembok yang luas itu. Orang Israel bertemu di area Bait Suci dan diakhiri dengan ucapan syukur dan pengorbanan. Karya ilmiah ini menggunakan metodologi penelitian teks dengan genre naratif tertentu berupa laporan cerita. Laporan tentang penahbisan tembok Yerusalem ini tidak sedang mengungkapkan masalah atau penyelesaian. Teks tersebut hanya menggambarkan urutan kejadian (fakta) dalam peresmian tembok Yerusalem. Upacara peresmian tembok Yerusalem merupakan laporan dari Nehemia. Teks Nehemia 12:27-43 hanya menggambarkan peristiwa yang terjadi pada perayaan peresmian tembok Yerusalem. Makna teologis dalam penahbisan Tembok Yerusalem menurut Nehemia 12:27-43 menunjukkan peran Tuhan (Tuhan memberi sukacita, Tuhan membimbing perbaikan tembok Yerusalem), pentingnya mengucap syukur, dan pentingnya umat Tuhan dalam memuji Tuhan.